Copper nanocluster, preparation method and application thereof, hydrogenation catalyst and preparation method of 4-formylmorpholine
By using a precise structure of copper nanocluster catalyst, the problem of low carbon dioxide conversion efficiency was solved, and the efficient coupling hydrogenation reaction between carbon dioxide and morpholine was achieved, and 4-formylmorpholine was prepared, demonstrating the catalytic performance and recycling performance. Improvement.
Patent Information
- Application Number
- CN202310847621.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to efficiently and selectively catalyze the conversion of carbon dioxide into useful chemicals, resulting in low carbon dioxide fixation efficiency.
Copper nanoclusters with precise atomic stacking structure are used as catalysts to prepare copper nanoclusters by combining with thiophenol and organophosphorus ligands and apply them to hydrogenation catalysts for catalyzing carbon dioxide and morpholine. Coupled hydrogenation reaction to prepare 4-formylmorpholine.
It has achieved efficient activation and conversion of carbon dioxide, excellent catalytic performance, and green and efficient preparation methods, and has good recycling performance.
Smart Images

Figure CN119306745A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalytic chemistry, and in particular to a copper nanocluster and a preparation method and application thereof, a hydrogenation catalyst and a preparation method of 4-formylmorpholine. Background Art
[0002] As a sustainable resource small molecule, carbon dioxide can be efficiently converted into high-value-added chemicals, which can alleviate the problem of over-reliance on fossil energy and environmental problems caused by carbon dioxide emissions. However, due to factors such as the thermodynamic stability and kinetic inertness of carbon dioxide, the current production process of the chemical industry using carbon dioxide as raw material only consumes a very small part of the total carbon dioxide emitted by human activities. How to efficiently, selectively and greenly catalyze carbon dioxide into useful chemicals and even high-end materials in large-scale industrial processes is very important to truly fix carbon dioxide. In the carbon dioxide molecule, two oxygen atoms and one carbon atom form two σ bonds through sp hybridization. The non-hybridized p orbital of the carbon atom and the p hybrid orbital of the oxygen atom have two three-center four-electron delocalized π bonds. Since the carbon atom in carbon dioxide is in the highest valence state and has a high first ionization energy (~14eV), a suitable catalyst is needed to activate the carbon dioxide molecule.
[0003] Metal clusters are usually composed of several to hundreds of metal atoms, in the sub-nanometer size range, with a certain number of atoms and precise atomic-level structure, unique electronic structure and molecular-like energy level structure. Compared with traditional bulk or particle catalysts, metal clusters are small in size, large in specific surface area, and have more surface active sites. There is synergy between metals and between metals and ligands, which makes them an ideal green catalytic material. The catalytic performance of metal clusters is completely different from that of nanoparticle catalysts and single-atom catalysts, providing a new material basis for regulating catalytic performance, a new research system for solving key scientific problems that traditional bulk or particle catalysts and single-atom catalysts have failed to solve, and bringing new research ideas and scientific methods for the activation and conversion of resource small molecules. We obtained copper clusters with atomically precise structures by precisely controlling the synthesis conditions. Such clusters have the advantages of precise atomic stacking structure, clear reaction sites, green synthesis, and high efficiency. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of difficulty in activating carbon dioxide molecules in the prior art, and to provide a copper nanocluster and a preparation method and application thereof, a hydrogenation catalyst and a preparation method of 4-formylmorpholine. The copper nanocluster has a precise atomic stacking structure, a clear reaction site, and is green and efficient in synthesis.
[0005] In order to achieve the above object, the present invention provides a copper nanocluster, the molecular formula of which is Cu m X x Y y , wherein X is an organophosphorus ligand, Y is a thiophenol ligand, m is 13, x is 4-7, and y is 3-12.
[0006] The second aspect of the present invention provides a method for preparing the copper nanoclusters according to the first aspect of the present invention, the preparation method comprising:
[0007] (1) first mixing a copper source, an organophosphorus ligand and a thiophenol ligand in a solvent to obtain a copper cluster complex solution;
[0008] (2) secondly mixing the copper cluster complex solution with the sodium borohydride solution, separating, washing and purifying to obtain a copper cluster precursor;
[0009] (3) culturing the copper cluster precursor into single crystals to obtain nanoclusters;
[0010] Preferably, the structural formula of the thiol ligand is,
[0011]
[0012] Among them, R4, R5, R6, R7, R8, and R9 are each independently selected from at least one of hydrogen, halogen, C1-C3 alkyl, acyl, and thiol, and at least one is selected from thiol.
[0013] The third aspect of the present invention provides an application of the copper nanoclusters described in the first aspect in the preparation of a hydrogenation catalyst.
[0014] The fourth aspect of the present invention provides a hydrogenation catalyst, which comprises the copper nanoclusters described in the first aspect of the present invention and an optional carrier.
[0015] A fifth aspect of the present invention provides a method for preparing 4-formylmorpholine, the method comprising: contacting morpholine, a catalyst, phenylsilane and carbon dioxide in the presence of a solvent;
[0016] The catalyst is the catalyst described in the fourth aspect of the present invention.
[0017] Through the above technical solution, the present invention has the following beneficial effects:
[0018] The copper nanoclusters with the structure of the present invention have a precise atomic stacking structure, clear reaction sites and excellent performance in activating carbon dioxide molecules;
[0019] The copper nanoclusters of the present invention are prepared by the method of the present invention, which is green and efficient;
[0020] The copper nanoclusters of the invention are used to catalyze the coupling hydrogenation reaction of carbon dioxide and morpholine to prepare 4-formylmorpholine, and have excellent catalytic performance and recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a single crystal structure diagram of the copper cluster prepared in Example 1;
[0022] Figure 2 is the UV-visible spectrum of the copper cluster prepared in Example 2;
[0023] Figure 3 is the electrospray ionization mass spectrum of the copper clusters prepared in Example 2;
[0024] Figure 4 is a transmission electron microscopy image of the copper clusters prepared in Example 2 supported on a titanium dioxide substrate;
[0025] Figure 5 This is a diagram showing the effect of cyclic use of the copper cluster catalyst prepared in Example 1 for catalytic coupled hydrogenation of carbon dioxide. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] The present invention provides a copper nanocluster, the molecular formula of which is Cu m X x Y y , wherein X is an organophosphorus ligand, Y is a thiophenol ligand, m is 13, x is 4-7, and y is 3-12.
[0028] The copper nanoclusters with the structure of the present invention have a precise atomic stacking structure, clear reaction sites and excellent performance in activating carbon dioxide molecules;
[0029] In the present invention, the organic phosphine ligand has a wide range of options and can be a conventional choice in the art. According to a preferred embodiment of the present invention, the organic phosphine ligand has a structural formula of:
[0030]
[0031] Wherein, R1 is selected from hydrogen or phenyl; R2 is selected from hydrogen or phenyl; R3 is selected from halogen or hydrogen.
[0032] According to a preferred embodiment of the present invention, the organic phosphine ligand is selected from triphenylphosphine and / or 4-fluorophenylphosphine.
[0033] In the present invention, the structural formula of the thiophenol ligand is:
[0034]
[0035] Wherein, R4, R5, R6, R7, R8, and R9 are each independently selected from at least one of hydrogen, halogen, C1-C3 alkyl, acyl, and thiol, and at least one is selected from thiol.
[0036] According to a preferred embodiment of the present invention, the thiophenol ligand is selected from at least one of 2-chlorothiophenol, 2,5-dimethylthiophenol, 2,4-dichlorothiophenol, 2-bromothiophenol, 4-acetamidothiophenol and 1,3-benzenedithiophenol.
[0037] According to a preferred embodiment of the present invention, x is 4 or 7.
[0038] According to a preferred embodiment of the present invention, y is 3 or 12.
[0039] The method for preparing the copper nanoclusters of the present invention is not particularly limited. According to a preferred embodiment of the present invention, the method for preparing the copper nanoclusters comprises:
[0040] (1) first mixing a copper source, an organophosphorus ligand and a thiophenol ligand in a solvent to obtain a copper cluster complex solution;
[0041] (2) secondly mixing the copper cluster complex solution with the sodium borohydride solution, separating, washing and purifying to obtain a copper cluster precursor;
[0042] (3) Cultivating the copper cluster precursor into single crystals to obtain nanoclusters.
[0043] According to a preferred embodiment of the present invention, the structural formula of the thiol ligand is:
[0044]
[0045] Among them, R4, R5, R6, R7, R8, and R9 are each independently selected from at least one of hydrogen, halogen, C1-C3 alkyl, acyl, and thiol, and at least one is selected from thiol.
[0046] The copper nanoclusters of the present invention can be obtained by the method of the present invention, and the preparation is green and efficient.
[0047] In the present invention, as long as the purpose of the present invention can be achieved, in step (1), there is no particular restriction on the weight ratio of the copper source, the organophosphorus ligand, the thiophenol ligand and the solvent. According to a preferred embodiment of the present invention, in step (1), the weight ratio of the copper source, the organophosphorus ligand, the thiophenol ligand and the solvent is 1:0.7-1:0.3-0.5:40-50, for example, 1:0.8:0.3:0.45. By adopting the above preferred embodiment, the preparation efficiency of copper nanoclusters can be further improved.
[0048] In the present invention, the optional range of the copper source is relatively wide. According to a preferred embodiment of the present invention, the copper source is a copper salt, preferably at least one of copper acetate, copper chloride, copper perchlorate, copper tetrafluoroborate tetraacetonitrile and copper acetylacetonate.
[0049] In the present invention, the solvent has a wide range of selectable solvents. According to a preferred embodiment of the present invention, the solvent is selected from at least one of acetonitrile, dichloromethane, methanol, ethanol, acetone and tetrahydrofuran. By adopting the above preferred embodiment, the preparation efficiency of copper nanoclusters can be further improved.
[0050] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular restriction on the volume ratio of the copper cluster complex solution to the sodium borohydride solution, and the volume ratio of the copper cluster complex solution to the sodium borohydride solution is 1:0.5-2. By adopting the above preferred embodiment, the preparation efficiency of copper nanoclusters can be further improved.
[0051] According to a preferred embodiment of the present invention, the mass concentration of the sodium borohydride solution is 50%-98%.
[0052] The solvent of the sodium borohydride solution in the present invention can be selected from a wide range. According to a preferred embodiment of the present invention, the solvent of the sodium borohydride solution is at least one of methanol, ethanol and water.
[0053] According to a preferred embodiment of the present invention, the first mixing conditions include: temperature of 20-40° C.; time of 10-30 minutes.
[0054] In the present invention, the second mixing method is to quickly add the copper cluster complex solution into the sodium borohydride solution.
[0055] According to a preferred embodiment of the present invention, the second mixing conditions include: temperature of 20-40° C.; time of 1-5 minutes.
[0056] In the present invention, the separation method can be a conventional choice in the art, such as filtration or centrifugation.
[0057] In the present invention, the washing method can be a conventional choice in the art, for example, washing with a detergent and then centrifuging for 2-10 times, preferably using different solvents for 1-5 times of washing.
[0058] According to a preferred embodiment of the present invention, the detergent is selected from at least one of n-hexane, acetone, acetonitrile, methanol, ethanol and dichloromethane.
[0059] In the present invention, the purification method can be selected from a range of options. According to a preferred embodiment of the present invention, the purification method is thin layer chromatography, and the developing solvent of the thin layer chromatography is preferably selected from at least one of methanol, ether, ethyl acetate and petroleum ether.
[0060] In the present invention, as long as the purpose of the present invention can be achieved, no special requirements are made on the single crystal cultivation method. According to a preferred embodiment of the present invention, the single crystal cultivation method is a vapor diffusion method.
[0061] According to a preferred embodiment of the present invention, dichloromethane, n-hexane, cyclohexane, toluene, or ether solvents are used for gas phase diffusion.
[0062] According to a preferred embodiment of the present invention, the conditions for the gas phase diffusion include: a temperature of 4-25° C. and a time of 2-30 days.
[0063] The invention provides an application of the copper nanoclusters in the preparation of hydrogenation catalysts.
[0064] The present invention provides a hydrogenation catalyst, which comprises the copper nanoclusters described in the present invention and an optional carrier.
[0065] According to a preferred embodiment of the present invention, the carrier is TiO2.
[0066] The invention provides a method for preparing 4-formylmorpholine, which comprises: in the presence of a solvent, allowing morpholine, a catalyst, phenylsilane and carbon dioxide to contact and react;
[0067] The catalyst is the catalyst described in the present invention.
[0068] The copper nanoclusters of the invention are used to catalyze the coupling hydrogenation reaction of carbon dioxide and morpholine to prepare 4-formylmorpholine, and have excellent catalytic performance and recycling performance.
[0069] According to a preferred embodiment of the present invention, the solvent for the contact reaction is selected from dioxane and / or acetonitrile.
[0070] In the present invention, the contacting conditions may be conventionally selected in the art.
[0071] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: the pressure of carbon dioxide is 1-4 MPa, preferably 2-3 MPa.
[0072] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction temperature is 50-100°C, preferably 60-100°C.
[0073] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction time is 5-20 hours, preferably 10-18 hours.
[0074] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: the molar ratio of morpholine, phenylsilane and catalyst is 1:2-5:0.04-0.1%.
[0075] The present invention will be described in detail below through examples.
[0076] In the following examples, all raw materials are commercially available unless otherwise specified;
[0077] The model of the single crystal diffractometer used to test the single crystal is D8 ADVANCE, manufactured by Bruker of Germany, the test temperature is 173K, the light source is a molybdenum target, and the analysis software for the crystal data uses the SHELXTL software package.
[0078] The model of the UV-visible spectrometer is UV-1800, the manufacturer is Shimadzu Corporation of Japan, and the scanning wavelength range is 250-1000nm.
[0079] The model of the mass spectrometer is Waters QT, manufactured by Waters Company of the United Kingdom. The spray voltage is 2.2 kV, and the spray source temperature is stabilized at 70°C.
[0080] The model of the transmission electron microscope is JEM 2100, manufactured by Japan Jeol Company, and the electron beam voltage during the test is 200 kV.
[0081] The gas chromatograph model was 9860C, the TCD detector was equipped with Plot Q and TDX-1 columns, hydrogen was used as carrier gas, and the chromatograph was automatically sampled for online analysis of the reaction products.
[0082] Example 1
[0083] 100 mg of tetrafluoroborate tetraacetonitrile copper and 100 mg of triphenylphosphine are added to a 50 ml round-bottom flask, copper salt is dissolved with 4 ml of acetonitrile and 1 ml of dichloromethane, stirred for 30 minutes, 30 microliters of 2,5-dimethylthiophenol are added, stirred for 30 minutes, sodium borohydride solution (100 mg of sodium borohydride is dissolved in 5 ml of methanol solution) is quickly added, stirred at room temperature for 3 hours, a red precipitate is obtained, washed with normal hexane and centrifuged 3 times, washed with methanol and centrifuged 2 times. Then thin layer chromatography is used, dichloromethane and petroleum ether are used as developing agents, and the separated product is obtained to obtain a high-purity cluster. The obtained high-purity cluster is dissolved in 5 ml of dichloromethane solution, 3 ml of normal hexane is added, and the solution is volatilized and diffused at 20 ℃ by gas phase volatilization. After 3 days, a block single crystal is obtained, and the yield is 50%. This single crystal is a copper cluster with 13 copper atoms protected by 3 2,5-dimethylthiophenols and 7 triphenylphosphine.
[0084] Crystal structure diagram Figure 1 .
[0085] Example 2
[0086] 100 mg of tetrafluoroborate tetraacetonitrile copper and 100 mg of triphenylphosphine were added to a 50 ml round-bottom flask, and the copper salt was dissolved with 4 ml of acetonitrile and 1 ml of dichloromethane. After stirring for 30 minutes, 30 μl (30.6 mg) of 2,4-dichlorobenzenethiol was added. After stirring for 30 minutes, sodium borohydride solution (100 mg of sodium borohydride dissolved in 5 ml of methanol solution) was quickly added. After stirring at room temperature for 4 hours, a red precipitate was obtained by filtration, washed with n-hexane and centrifuged 3 to 5 times, and then washed with methanol and centrifuged 1 to 2 times. Then, the product was separated by thin layer chromatography using dichloromethane and ether as developing agents to obtain high-purity clusters. The obtained high-purity cluster was dissolved in 5 ml of dichloromethane solution, 3 ml of n-hexane was added, and the solution was evaporated and diffused at 20°C. After 3 days, a block single crystal was obtained with a yield of 50%. This single crystal is a copper cluster with 13 copper atoms protected by 3 2,4-dichlorothiophenols and 7 triphenylphosphines. The UV-visible spectrum is shown in Figure 2 ; Mass spectrum see Figure 3 ; Transmission electron microscopy images are shown in Figure 4 .
[0087] Example 3
[0088] 100 mg of tetrafluoroborate tetraacetonitrile copper and 100 mg of 4-fluorophenylphosphine were added to a 50 ml round-bottom flask, and the copper salt was dissolved with 5 ml of acetonitrile and 2 ml of dichloromethane. After stirring for 30 minutes, 30 microliters of 2,4-dichlorobenzenethiol were added. After stirring for 30 minutes, sodium borohydride solution (100 mg of sodium borohydride dissolved in 5 ml of methanol solution) was quickly added. After stirring at room temperature for 3 to 4 hours, a red precipitate was obtained, which was washed with n-hexane and centrifuged 3 to 5 times, and then washed with methanol and centrifuged 1 to 2 times. Then, the product was separated by thin layer chromatography using dichloromethane and ether as developing agents to obtain high-purity clusters. The obtained high-purity cluster was dissolved in 5 ml of dichloromethane solution, 3 ml of n-hexane was added, and the solution was evaporated and diffused in the gas phase at 20°C. After 3 days, a block single crystal was obtained with a yield of 50%. This single crystal is a copper cluster with 13 copper atoms protected by 3 2,4-dichlorobenzenethiols and 7 4-fluorophenylphosphines.
[0089] Example 4
[0090] 100 mg of tetrafluoroborate tetraacetonitrile copper and 100 mg of 4-fluorophenylphosphine are added to a 50 ml round-bottom flask, and the copper salt is dissolved with 5 ml of acetonitrile and 2 ml of dichloromethane. After stirring for half an hour, 30 microliters of phenylethyl mercaptan are added. After stirring for 30 minutes, sodium borohydride solution (100 mg of sodium borohydride is dissolved in 5 ml of methanol solution) is quickly added. After stirring at room temperature for 3 to 4 hours, a red precipitate is obtained, which is washed with normal hexane and centrifuged for 3 to 5 times, and then washed with methanol and centrifuged for 1 to 2 times. Then thin layer chromatography is used, using dichloromethane and ether as developing agents, and the product is separated to obtain a high-purity cluster. The obtained high-purity cluster is dissolved in 6 ml of dichloromethane solution, 4 ml of normal hexane is added, and the solution is volatilized and diffused at 20°C. After 3 days, a block single crystal is obtained, and the yield is 50%. This single crystal is a copper cluster with 13 copper atoms protected by 3 phenylethyl mercaptan and 7 4-fluorophenylphosphine.
[0091] Example 5
[0092] 100 mg of copper acetylacetonate was added to a 100 ml round-bottom flask, the metal salt was dissolved in 30 ml of methanol, and then 60 mg of silver nitrate was added. After stirring for 15 minutes, 80 microliters of 1,3-benzenedithiol was added. After stirring for 15 minutes, 10 ml of dichloromethane solution containing 1.2 g of triphenylphosphine was added. After stirring for 30 minutes, sodium borohydride solution (70 mg of sodium borohydride dissolved in 5 ml of aqueous solution) was quickly added. After stirring at room temperature for 10 hours, a red precipitate was obtained, which was washed with ethanol and centrifuged 5 to 6 times. Then, thin layer chromatography was used, using dichloromethane and petroleum ether as developing agents, to separate the product to obtain high-purity clusters. The obtained high-purity clusters were dissolved in 10 ml of dichloromethane solution, 6 ml of n-hexane was added, and the solution was volatilized and diffused at 20°C. After one week, brick-red crystals were obtained with a yield of 50%. This crystal is a copper cluster with 12 copper atoms protected by 12 benzenedithiols and 4 triphenylphosphines.
[0093] Example 6
[0094] 4 mmol of morpholine was weighed and added to 10 ml of dioxane solution. After mixing and stirring, 10 mmol of phenylsilane was added, and then 2 micromol of the copper cluster catalyst prepared in Example 1-5 was added. The above mixture was transferred to a high-pressure reactor, filled with 2 MPa of carbon dioxide, and reacted for 10 hours at a temperature of 100 degrees and a stirring speed of 600 rpm to obtain 4-formylmorpholine.
[0095] Each copper cluster catalyst has a similar catalytic effect. Figure 5 This is the result of carbon dioxide coupling hydrogenation catalyzed by the copper cluster prepared in Example 1. It can be seen that the formylation yield is 80%.
[0096] Example 7
[0097] The same as Example 9, except that the catalyst prepared in Example 2 was replaced by a copper cluster catalyst loaded with titanium dioxide, and the yield of 4-formylmorpholine was 85%.
[0098] It can be seen from the results of the examples that the Cu protected by the ligand of the present invention 13 Example 1 of the cluster has a significantly better effect.
[0099] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copper nanocluster, characterized in that: The molecular formula of the copper nanocluster is Cu m X x Y y , wherein X is an organophosphorus ligand, Y is a thiophenol ligand, m is 12 or 13, x is 4-7, and y is 3-12.
2. The copper nanoclusters according to claim 1, wherein The structural formula of the organophosphine ligand is: wherein R1 is selected from hydrogen or phenyl; R2 is selected from hydrogen or phenyl; R3 is selected from halogen or hydrogen; Preferably, the organophosphine ligand is selected from triphenylphosphine and / or 4-fluorophenylphosphine; and / or The structural formula of the thiophenol ligand is: wherein R4, R5, R6, R7, R8, and R9 are each independently selected from at least one of hydrogen, halogen, C1-C3 alkyl, acyl, and thiol, and at least one is selected from thiol; Preferably, the thiophenol ligand is at least one selected from 2-chlorothiophenol, 2,5-dimethylthiophenol, 2,4-dichlorothiophenol, 2-bromothiophenol, 4-acetamidothiophenol and 1,3-benzenedithiol.
3. The copper nanoclusters according to claim 1 or 2, wherein: The x is 4 or 7, and the y is 3 or 12.
4. The method for preparing copper nanoclusters according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) first mixing a copper source, an organophosphorus ligand and a thiophenol ligand in a solvent to obtain a copper cluster complex solution; (2) secondly mixing the copper cluster complex solution with the sodium borohydride solution, separating, washing and purifying to obtain a copper cluster precursor; (3) culturing the copper cluster precursor into single crystals to obtain nanoclusters; Preferably, the structural formula of the thiol ligand is, Among them, R4, R5, R6, R7, R8, and R9 are each independently selected from at least one of hydrogen, halogen, C1-C3 alkyl, acyl, and thiol, and at least one is selected from thiol.
5. The preparation method according to claim 4, wherein: In step (1), the weight ratio of the copper source, the organophosphorus ligand, the thiophenol ligand and the solvent is 1:0.7-1:0.3-0.5:40-50.
6. The preparation method according to claim 4 or 5, wherein: The copper source is a copper salt, preferably at least one of copper acetate, copper chloride, copper perchlorate, copper tetrafluoroborate tetraacetonitrile and copper acetylacetonate; and / or The solvent is selected from at least one of acetonitrile, dichloromethane, methanol, ethanol, acetone and tetrahydrofuran.
7. The preparation method according to any one of claims 4 to 6, wherein: In step (2), the volume ratio of the copper cluster complex solution to the sodium borohydride solution is 1:0.5-2; Preferably, the mass concentration of the sodium borohydride solution is 50%-98%, and more preferably the solvent of the sodium borohydride solution is at least one of methanol, ethanol and water.
8. The preparation method according to any one of claims 4 to 7, wherein: The purification method is thin layer chromatography, and preferably the developing solvent of the thin layer chromatography is selected from at least one of methanol, ether, ethyl acetate and petroleum ether.
9. The preparation method according to any one of claims 4 to 8, wherein: The single crystal culture method is a vapor diffusion method, preferably using dichloromethane, n-hexane, cyclohexane, toluene, ether solvent for vapor diffusion, and more preferably the vapor diffusion conditions include: temperature of 4-25°C and time of 2-30 days.
10. Use of the copper nanoclusters according to any one of claims 1 to 3 in the preparation of hydrogenation catalysts.
11. A hydrogenation catalyst, characterized in that The catalyst comprises the copper nanoclusters according to any one of claims 1 to 3 and an optional carrier.
12. A method for preparing 4-formylmorpholine, characterized in that: The method comprises: in the presence of a solvent, contacting morpholine, a catalyst, phenylsilane and carbon dioxide for reaction; The catalyst is the catalyst according to claim 11; Preferably, the solvent is selected from dioxane and / or acetonitrile.
13. The method according to claim 12, wherein: The conditions of the contact reaction include: The pressure of carbon dioxide is 1-4 MPa, preferably 2-3 MPa; and / or The reaction temperature is 50-100°C, preferably 60-100°C; and / or The reaction time is 5-20h, preferably 10-18h; and / or The molar ratio of morpholine, phenylsilane and catalyst is 1:2-5:0.04-0.1%.